A prática da psicologia nas políticas públicas de ressocialização em Pernambuco - Santana, Silvana Maria de (2016)
The present study aims investigating the psychological clinic action within the scope of Public Policies of resocialization of adult prison population. For this purpose, it characterizes the prison institution and the process of incarceration, also the description of Public Policies of resocialization in the prison system of Pernambuco. This context is the basis for comprehending the psychologists'actions, having been gathered their narratives, aiming to establish a dialog with the actual policies. The insertion of psychologists in this field of work, in Brazil, occurred in the decade of 1970, in forensic psychiatric hospitals to psychological reports, but became permanent in 1984 due to the Law of Penal Executions which requires the participation of these professionals in the Classification Technical Committee to perform the toxicological examination. According to the Ministry of Labour and the Federal Council of Psychology, this area of work belongs to the Forensic Psychology and is not limited to psychological evaluation, albeit it is still hegemonic nationwide. The psychologists, in this context, face demands aimed at reintegrating men and women to the society, which requires engagement and assisting from psychology in the state policies for this population. The fieldwork has been done in both a women's and a men's PU (Prison Unit); we made use of the cartographic method, in that it allows us to trace the experiences, narrated by the participating professionals and the involvement of the researcher in these cases. The results has been analyzed making use of understanding hermeneutics and the dialog with the diversity of this field, which is juridical, social and clinical. We concluded that the activities developed by these psychologists in those PUs, when possible, occurred in poor conditions with no decent place, both physical and subjective, to the psychological science and are hampered by the growing precarious state of the labour ties, the power relations haracterised by legal hierarchy, the powerlessness against and the violence and violations of fundamental human rights. The successful contribuitions are quite particular and are lost amid the lack of a integrated project between various areas of knowledge and denounce as well the lack of a resocialization project that actually meet the expectations of the convicted, the justice and society. This scenario shows the pressing need of public policies that meet the intended resocialization goals.